Essential grammar in use + CD - Murphy, Raymond (Cambridge Cambridge University press, 2009)
Using clear examples and easy to follow exercices, covering all the areas of grammar that an elementary level students needs.
Contents, index.
Keywords: Teaching; Classroom Techniques; English - foreign language; Grammar; Learning